Uganda : 2021 Article IV Consultation and First Review under the Extended Credit Facility Arrangement and Requests for Modifications of Performance Criteria-Press Release; Staff Report; and Statement by the Executive Director for Uganda. (IMF Staff Country Reports; Country Report ;, 2022)
The authorities have reacted to the COVID-19 crisis in an appropriate manner, including through increased spending on health and a rollout of the vaccination program. Nevertheless, the deterioration of socio-economic indicators during the pandemic could create scars that would significantly lower growth if left unaddressed.